Characterization of carbon fiber-reinforced thermoplastic and thermosetting polyimide matrix composites manufactured by using various synthesized PI precursor resins - AKIN, EMRE; ÇAKIR, MUSTAFA (Elsevier Ltd, 2022)
Currently, it is important to manufacture thermoplastic advanced composites with high mechanical and thermal properties because of their higher impact resistance than thermoset composites. In this study, carbon fiber (CF)-reinforced thermoplastic and thermosetting polyimide (PI) matrix composites were manufactured by vacuum bagging followed by compression molding. Before the manufacturing process, prepregs were also prepared with various PI precursor resins by using two-step impregnation. These precursors were synthesized as poly (amic acid) (PAA), polyester amine salts (PEAS) and poly (amic acid) ammonium salts (PAAS). The PAAS precursor resin was applied as a novel method for manufacturing CF-reinforced PI matrix advanced composites. The advanced thermoplastic composite obtained from the PAAS precursor (PAAS-T) exhibited superior mechanical properties and enhanced thermal properties (near the thermal properties of thermoset advanced composites) in comparison to the other advanced composites in this study and those in the literature. However, the NA-terminated PAAS precursor (thermosetting PI precursor) did not exhibit a similar effect in terms of mechanical properties. On the other hand, the thermosetting composites exhibited highly enhanced storage modulus values up to 400 °C and outstanding thermal stability at TGA. The thermosetting composite that was obtained from the NA-terminated PAA precursor resin exhibited high mechanical properties besides its thermal properties. © 2021
Keywords: Carbon fiber/polyimide composite; High-performance thermosetting and thermoplastic advanced composites; NA-terminated poly(amic acid) precursor; poly(amic acid) ammonium salt precursor resin; Two-step impregnation